Manajemen Dakwah Dewan Masjid Indonesia Kota Medan Dalam Meningkatkan Sumber Daya Manusia Pengurus Masjid Di Kota Medan - Rustam Effendi Gorat; Waizul Qarni (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This research aims to examine the human resources (HR) improvement program for mosque administrators implemented by the Indonesian Mosque Council (DMI) of Medan City. The main focus of this research is to identify the challenges faced, the strategies used, and the impact of the program on the quality of mosque management. The research results show that increasing human resources for mosque administrators in Medan City faces various obstacles, such as a lack of understanding of modern mosque management, financial limitations, and low regeneration of administrators. DMI Medan City overcomes these challenges through training, mentoring and collaboration approaches with various parties. However, the effectiveness of the program is still limited by the lack of participation of mosque administrators, budget limitations, and less than optimal support. This research contributes to the development of a model for improving human resources for mosque administrators that is more relevant to the urban context, and can be a reference for DMI Medan City policy to optimize the role of mosque administrators.